ANALISIS PERILAKU BERBELANJA ONLINE KONSUMEN MUSLIM DALAM PERSPEKTIF GENDER DI PROVINSI RIAU (Ditinjau dari Perceived Risk, Service Infrastructure, dan Acquisition Utility) - Fachrurrozi -; Alchudri - (Marwah: Jurnal Perempuan, Agama dan Jender, 2016)
This study aims to determine the effect of perceived risk, service infrastructure, acquisition utility to the online shopping behavior of students in the province of Riau and to determine differences in perceived risk, service infrastructure, acquisition utility and online shopping behavior between male students and female in Riau Province. The total sample is 250 respondents. Independent variable is perceived risk (X1), service infrastruktur (X2), acquistion utility (X3) and dependen variavle is online shopping behavior (Y). Data analysis using multiple linear regression analysis and one way ANOVA. The results showed perceived risk influence on online shopping behaviour, service infrastructure influence on online shopping behaviour, acquisition utility influence on online shopping behaviour, results of hypothesis testing using ANOVA showed that there are differences in perceived risk, service infrastructure, acquisition utility and online shopping behavior between male students and female students.